Extensive bronchial occlusion with N‐butyl‐2‐cyanoacrylate for bronchopleural fistula and a destroyed lung. Issue 1 (12th November 2019) - Kaminuma, Yasunori; Tanahashi, Masayuki; Suzuki, Eriko; Yoshii, Naoko; Niwa, Hiroshi
Abstract : A 72‐year‐old Japanese man who had undergone resection of a left upper lung carcinoma developed chronic empyema with bronchopleural fistula and destroyed lung 12 years after surgery. Open‐window thoracotomy and bronchial occlusion with an endoscopic Watanabe spigot (EWS) were performed to control infection. However, the EWS was easily dislodged due to remarkable bronchial deformation, and he experienced repeated episodes of pneumonia. We performed extensive bronchial filling with N‐butyl‐2‐cyanoacrylate. Stable occlusion was achieved, and there was no recurrence of pneumonia. N‐butyl‐2‐cyanoacrylate was a useful embolic agent because it moulded to the shape of the tracheal lumen and remained in place. Abstract : Here, we report a case of chronic empyema with bronchopleural fistula and destroyed lung in which bronchial occlusion with N‐butyl‐2‐cyanoacrylate and lipiodol resulted in the improvement of respiratory distress and recurrent pneumonia.